Hardware development of low power circuits for multilevel converter applications - Tan, Daniel Xin Ru (2015)
In the past decades, renewable energy system has become the focus research area due to the fact that there is an increased concern on environmental issues and also the depleting fossil resources. Wind turbine and photovoltaic systems have become the most common type of grid connected renewable energy systems. With that in mind, multilevel inverters have increasing been considered in variable speed wind turbine and photovoltaic systems. Multilevel converters are well-known for its power conversion ability especially for medium high power drives applications in the industry. As multilevel converters are able to increase the output voltage without increasing the voltage rating of switching devices which allow direct connection to the grid without the usage of those bulky transformers. In addition, multilevel inverters synthesis stair case output voltage which contributes to a smoother sinusoidal voltage and also in the process reducing the harmonic effects. However, one of the disadvantages is the increase in component counts required especially the power semiconductor switches. Hence multiple isolated power supplies are required to supply the comparator circuits, deadtime circuits and isolated gate drivers for these IGBT/MOSFET switches. In this Final Year Project, the hardware of low power circuits have been developed which will be used to verify on the application on flyback converters to design for multiple isolated power supplies. Literature reviews and studies on power electronics, flyback transformers and sinusoidal pulse-width modulation. The area of interests are on the 3-level 3-phase Neutral-Point-Clamped (NPC) Inverter and design of hybrid flyback converter circuit to create multiple output voltages with isolated groundings for the gate driver circuits to reduce the overall cost of the system.